Assessment of the Genetic Diversity of Xanthomonas axonopodis pv. phaseoli and Xanthomonas fuscans subsp. fuscans as a Basis To Identify Putative Pathogenicity Genes and a Type III Secretion System of the SPI-1 Family by Multiple Suppression Subtractive Hybridizations - Alavi, Seyed Mehdi (American Society for Microbiology (ASM), 2008)
Fluorescent amplified fragment length polymorphism revealed that strains of Xanthomonas axonopodis pv. phaseoli and Xanthomonas fuscans subsp. fuscans are genetically distinct and can be grouped into four genetic lineages. Four suppression subtractive hybridizations were then performed to isolate DNA fragments present in these bean pathogens and absent from closely related xanthomonads. Virulence gene candidates were identified such as homologs of hemagglutinins, TonB-dependent receptors, zinc-dependent metalloproteases, type III effectors, and type IV secretion system components. Unexpectedly, homologs of the type III secretion apparatus components (SPI-1 family), usually reported in animal pathogens and insect symbionts, were also detected.